2015
DOI: 10.2196/mhealth.4393
|View full text |Cite
|
Sign up to set email alerts
|

A Novel System for Supporting Autism Diagnosis Using Home Videos: Iterative Development and Evaluation of System Design

Abstract: BackgroundObserving behavior in the natural environment is valuable to obtain an accurate and comprehensive assessment of a child’s behavior, but in practice it is limited to in-clinic observation. Research shows significant time lag between when parents first become concerned and when the child is finally diagnosed with autism. This lag can delay early interventions that have been shown to improve developmental outcomes.ObjectiveTo develop and evaluate the design of an asynchronous system that allows parents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 25 publications
1
63
0
1
Order By: Relevance
“…Still, clinical judgment is often based on a two-way exchange of information between patients and clinicians rather than a single opportunity to share information. Although not utilized in this initial validation study, the NODA system also includes a feature to allow raters to request additional information from families (e.g., re-recording a scenario with additional social presses from the parent), which shows up in the form of an alert within the family’s NODA application (see Nazneen et al, 2015, for more details). This feature provides an additional opportunity for the rater to solicit clinically relevant information to clarify the nature of the child’s behavior and perhaps improve the accuracy and confidence of clinical judgment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Still, clinical judgment is often based on a two-way exchange of information between patients and clinicians rather than a single opportunity to share information. Although not utilized in this initial validation study, the NODA system also includes a feature to allow raters to request additional information from families (e.g., re-recording a scenario with additional social presses from the parent), which shows up in the form of an alert within the family’s NODA application (see Nazneen et al, 2015, for more details). This feature provides an additional opportunity for the rater to solicit clinically relevant information to clarify the nature of the child’s behavior and perhaps improve the accuracy and confidence of clinical judgment.…”
Section: Discussionmentioning
confidence: 99%
“…interact with your child playfully; say your child’s name to get their attention; ask your child where something is in the room; give your child time to initiate or respond; point at something and direct your child’s attention to it). Pilot studies demonstrated that these instructions improved the clinical utility of the videos (Nazneen et al, 2015). To avoid predisposing parents toward collecting examples of behaviors that indicate ASD (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…47 One study has even designed a diagnostic tool using home videos recorded by parents. 48 Specifically, a program in Kansas uses professional teams in the patient’s local community to perform standardized assessments, which are then presented to the family and a university-based medical center team that makes the final diagnostic assessment and provides recommendations via telemedicine. 42 As academic hospital centers rapidly expand their technological resources, telemedicine provides a modern venue for increasing accessibility to specialized services for children with developmental concerns.…”
Section: Additional Opportunities In Technology and Public Policymentioning
confidence: 99%
“…Most studies (39%) included £15 participants. 13,21,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] Fourteen studies had >15 but <25 participants, [54][55][56][57][58][59][60][61][62][63][64][65][66][67] and 14 studies had between 26 and 59 participants. [68][69][70][71][72][73][74][75][76][77][78][79][80][81] Three studies described the population but did not include the number of participants.…”
Section: Study Characteristicsmentioning
confidence: 99%